PS 17-61 MICROALBUMINURIA IS A GOOD SURROGATE ARTERIAL STIFFNESS MARKER IN NEVER TREATED NON-DIABETIC HYPERTENSIVES WITH NORMAL RENAL FUNCTION BUT HIGH SENSITIVITY CRP IS NOT. FROM THE KOREAN HYPERTENSION REGISTRY (KorHR). (September 2016) - Choi, Seonghoon
Abstract : Objective: hsCRP is well known inflammatory marker and relatd with artherosclerotic cardiovascular events. in MI and diabetic patients, there have so many evidences on the role of hsCRP, but is still debates related with TOD in pure hypertensives. This cross-sectional anaylsis was aimed to analyze to determine the effect on PWV (well known TOD) by hsCRP level in Korean hyperensives never treated with non-diabetic normal renal function patients. Design and method: From KorHR registry, total 100 patients (M 75%, mean age 46.4) evaluated with simultaneously hsCRP, ACR, PWV study were enrolled. Mean microalbuminuria (MA) was defined by morning spot urine ACR (mg/g) according to National Kidney Foundation criteria and elevated hsCRP level was defined above median value (1.355 mg/L). PWV adjusted by age and mABP was used as a TOD event. Results: Mean ACR was 22.37+/-37.8. MA was observed in 28.2% patients, . Patients with MA showed elevated DBP (by office, ABPM, CBP) and low HDL-C, and increased PWV (all p < 0.05). But patients with increased hsCRP (28.2%) showed more higher waist circumflex and low HDL-C level but PWV was not statistically different. After adjusting age and mABP for PWV, the presence of MA showed independent factor related with more stiff artery (p = 0.039) but elevated hsCRP was not indendent factor (p = 0.343). Conclusions: In this Registry cross-sectional anaysis, the presence of microalbuminuria of non-diabetic hypertensives with normal renal function who never treated, is a independent factor of predicting arterial stiffness (TOD) but low grade inflammatory marker, hsCRP is not. This result indicate there is an indirect mechamism between low grade inflammation (hsCRP) and TOD of hypertension.